Evaluation of Puskesmas Information System at UPTD Puskesmas Talise Evaluation of the Puskesmas Information System at the Talise Health Center UPTD - Rahmiati (Yayasan Sinergi Kawula Muda, 2021)
Puskesmas as the spearhead of implementing health development in the regions in carrying out their programs require effective management starting from planning, implementing, monitoring, and evaluating the programs they run. Effective and efficient management requires information, the availability of information at the Puskesmas is produced by a Management Information System based on Puskesmas services (Anita et al, 2019). In the Regulation of the Minister of Health of the Republic of Indonesia Number. 31 of 2019 concerning the Puskesmas Information System, regulates a series of Puskesmas Information System activities which include Human Resources, Funds, Facilities and Infrastructure, Recording and Reporting. The type of research used in this research is qualitative research. The number of informants used were 3 people, namely key informants, regular informants, and additional informants. The purpose of this study was to identify and describe the information system of the Puskesmas at UPTD Puskesmas Talise. The results of the study indicate that; (1) The inputs in the implementation of SIP at the Talise Health Center are not adequate, as can be seen from the insufficient funds. (2) The process of implementing the SIP at the Talise Health Center has been carried out quite well. (3) The outputs in the implementation of the SIP at the Puskesmas Talise has not been achieved because there are still reports that are not timely and not accurate. The research suggestions are (1) that it is necessary to conduct planned and continuous training in order to obtain skilled and professional human resources in data processing using a computerized system.